Analisis Perpindahan Panas pada Sirkulasi Air Penyulingan Nilam dengan Tangki Bervolume 150 Liter: Heat Transfer Analysis on Circulating Patchouli Distilled Water with a 150 Liter Volume Tank - Zaky Assiddiqie; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Indonesia is the world’s main exporter of patchouli plants (Pogostemon Cablin Benth). Patchouli plants produce essential oil by distillation; this essential oil has a constituent component called patchouli alcohol and is widely used in the aromatic industry. Therefore, a patchouli refining process is needed so that Indonesia’s patchouli can improve its quality in the eyes of the world. The purpose of this research is to observe the process of cooling hot patchouli steam into patchouli oil to optimize the current process. This study's analytical method is a simulation approach with CFD software. 50 kg of dried patchouli leaves and stems will go through a combustion process and then be distilled in a 150 liter volume tank for 5 hours. During the distillation process, there is a heat transfer phenomenon called conduction and convection. The LMTD value was 327 K, the heat transfer rate was 103,39 W, the overall heat transfer was 223,45 W/m2K, the NTU value was 0,018, and the system's effectiveness was 0.89% using LMTD and the -NTU method.